Studying and Promoting Knowledge on Sustainable Agricultural Waste Management: A Case Study in Banhan Upper Secondary School and Surrounding Schools in Hongsa District, Xayaboury Province, Lao PDR - SITTHIVOHANE, Insavai; PHOUTTHAXAY, Phonesavanh; CHANTHAKHOUN, Vongpasith; ONSIMEAUNG, Anousone; THONGPASERT, Savath; MAHAVONGSANANH, Noy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The investigation took place at Banhan upper secondary school in the Hongsa district of Xayaboury Province. It spanned a duration of 12 months and involved providing TOT training on managing reused and recycled waste to 35 students and teachers at the school. Additionally, 48 trash bins were supplied and set up across 7 schools and 3 related offices. A school received a trash bin to collect recyclable waste that was set up for the students' practice. The findings presented that 94.71% with understanding index 1.24 SD of the students and teachers were displayed a good understanding and comprehended the project's activities, with 83.47% with sastisfacting index 0.77 SD expressing satisfaction. Only a small fraction, less than 5.29%, struggled with waste management and required further enhancement of their knowledge and skills. The waste collected from 10 locations comprising schools and offices underwent 8 rounds of 2 months collection. In total, 1,121.2 Kg of waste was disposed of, averaging 280.3 Kg per mounth. The waste output in schools increased due to the growing number of students and educators. Banhan upper secondary school accounted for the highest waste quantity output at 49.7 Kg/month (17.73%), followed by Monk lower secondary school at 36.2 Kg/month (12.91%), and Nasan primary school at 33.8 Kg/month (12.06%) and the least amount of waste was generated by the district office of Education and Sports only 13.7 Kg/month (4.89%) representively. The quantity of 4 categories of waste revealed that the burnable waste promoted largest quantity 149.9 Kg/month (4.99 Kg/day), connected by compost waste 71.4 Kg/month (2.38 Kg/day), Reusable waste 60 Kg/month (2 Kg/day) and harmful waste 2 Kg/month (0.07 Kg/day). Waste in a day per person was calculated from populalation of the institution in 8h a day (working day), result shown that district office of Natural Resource and Enviroment has a high significant in quantity of waste 0.0351 Kg (35.1 g)/person/day. Then, Phonchan primary school 0.0221 Kg (22.1 g)/person/day and Nasan primary School 0.0205 Kg (20.5g)/person/day, the lowest quantity of waste was Hongsa upper secondary school 0.0012 Kg (1.2 g)/person/day. Nevertheless, the primary emphasis of this research was on the quantities of waste can be reuse, aiming to enhance awareness among academic staff, teachers, and students. The goal is to ensure comprehension, discourage indiscriminate disposal of garbage, and promote waste reduction through practices such as reuse and recycling.